Contenção à pessoa idosa em ILPI’s: cuidado ou violência? - Santos, Bruna Suelem Mendes dos (2018)
Introduction: Much has been pointed out that in health institutions containment practices are considered care actions. When one speaks of care one can say that this means to preserve, to keep, to conserve, to support or to take care of. The restraint to the elderly person has, however, been understood in several ways. These include mechanisms and methods that, in some way, limit the person, reducing spontaneous body movement, understood as any restrictive measure of daily life. In this sense, the practice of containing older people has been commonly used in individuals with certain conditions of fragility, when others assume responsibility for them. Objectives: The purpose of this study is to understand the reasons that nurses are taking to restrain the elderly in Long-Term Care Institutions for the Elderly (ILPIs). Methods: We interviewed 32 nurses, who work in the region of Pará, Santa Catarina and São Paulo. Data collection and analysis of the proposed interviews used a qualitative methodology based on authors such as Minayo and Turano, who helped to understand the objective issues. Results: The research is based on the analysis of content of Bardin, through studies that made it possible to understand what nurses working in a long-term institution understand by containment. The work was categorized and organized into three themes based on the questionnaire response: a) the profile of the professionals interviewed; b) what the professionals understand by containment; c) care in the perspectives of the nurses interviewed. Conclusion: Through this study we identified that although the professionals have the conscience that is practiced is not beneficial to the elderly. They continue to use for lack of choice, due to institutional requirements, environmental conditions, mobilization equipment for the elderly, to avoid falls and often for lack of knowledge of the subject